Stance adverbials and adverbialization in Lithuanian academic discourse - Smetona, Antanas; Usonienė, Aurelija (Kalbotyra, 2012)
The purpose of the paper is to demonstrate the necessity of distinguishing a semantic-functional class of stance adverbials in Lithuanian. Following Biber et al. (1999) and Hasselgård (2010) an attempt is made to show that alongside circumstance adverbials there are also linking adverbials and stance adverbials in Lithuanian. The means of realization of stance adverbials in Lithuanian is not only adverbs but also so called modal words (galbūt‘maybe’, tikriausiai ‘most probably’), various particles (taigi ‘therefore’, visgi ‘still’, ‘nevertheless’), CTPs (manoma ‘it is believed’, natūralu ‘naturally’), various adverbial clauses (kaip matyti ‘as it is seen, as one can see’, kaip žinoma ‘as is known’) but also prepositional phrases (pasak X ‘according to X’). The article devotes much attention to the semantic classification of the basic types of stance adverbials, which has been illustrated by the language data collected from the Corpus of Academic Lithuanian (Corpus Academicum Lithuanicum – CorALit – http://coralit.lt). The paper also touches upon the process of adverbialization and its relationship to grammaticalization which presupposes the desemanticization and (inter)subjectivization of the linguistic expressions under analysis. Many Lithuanian verbal and adjectival CTPs like žinoma ‘it is known’, suprantama ‘it is understood’, tarkim ‘let’s say’ can develop into stance adverbials and further into discourse markers by losing any links to the original lexical meaning of the verb they have evolved from.
Keywords: adverbials; adverbialization; academic discourse; author stance; Corpus of Academic Lithuanian